2021
DOI: 10.1371/journal.pone.0254380
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping Arctic cetaceans from space: A case study for beluga and narwhal

Abstract: Emergence of new technologies in remote sensing give scientists a new way to detect and monitor wildlife populations. In this study we assess the ability to detect and classify two emblematic Arctic cetaceans, the narwhal (Monodon monoceros) and beluga whale (Delphinapterus leucas), using very high-resolution (VHR) satellite imagery. We analyzed 12 VHR images acquired in August 2017 and 2019, collected by the WorldView-3 satellite, which has a maximum resolution of 0.31 m per pixel. The images covered Clearwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Detecting whales in the imagery is either conducted manually 1 , 4 , 5 , 7 , or automatically 2 , 3 . A downside of the manual approach is that it is time-demanding, with manual counter often having to view hundred and sometimes thousands of square kilometres of open ocean.…”
Section: Background and Summarymentioning
confidence: 99%
“…Detecting whales in the imagery is either conducted manually 1 , 4 , 5 , 7 , or automatically 2 , 3 . A downside of the manual approach is that it is time-demanding, with manual counter often having to view hundred and sometimes thousands of square kilometres of open ocean.…”
Section: Background and Summarymentioning
confidence: 99%
“…Although UAS provide less spatial coverage than satellite images, they can allow more control over survey timing and surveying in overcast conditions, as well as higher spatial resolution, which can be of use for smaller marine mammals like sea otters ( Enhydra lutris ) or dolphins of the Cephalorhynchus genus. Nevertheless, the manual analysis of satellite and UAS imagery is time- and effort-intensive, for which automation can help ( Linchant et al, 2015 ; Hollings et al, 2018 ; Charry et al, 2021 ; Höschle et al, 2021 ). While Thums et al (2018) provided a comparative measure of time saved by their workflow, we recommend future automated marine mammal studies do the same, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the analysis of 425 km 2 (still a relatively small area in terms of marine mammal distribution) took 24 h to be analyzed with three replicates (eight hours per person) for the work of Thums et al (2018) , corresponding to 1.13 min per km 2 . Furthermore, Cubaynes et al (2019) reported three hours and 20 min to scan 100 km 2 at a 1:1,500 m. scale (2 min per km 2 ), and Charry et al (2021) reported an even slower rate of approximately 2.5 min per km 2 (at a 1:536 scale). While satellite images have allowed continental-scale abundance and distribution studies in remote locations ( e .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research using VHR satellite images to monitor cetaceans has increased since Abileah (2002) [13] and Fretwell et al. (2014) [14] pioneering studies, highlighting how VHR satellite imagery may help gather missing information about whales, and complement boat and aircraft surveys [3 , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] . There have been developments in using this technology in remote regions to estimate whale density [17] , detect strandings [21 , 24 , 25] , and count cetaceans [18] .…”
Section: Introductionmentioning
confidence: 99%